Implementation of Artificial Intelligence (AI) in Public Administration in the Era of the Industrial Revolution 4.0 - Salam, Rahmat (Global Writing Academica Researching and Publishing, 2023)
The use of Artificial Intelligence is quite commonly used by people, both to help with their daily lives and to help with their work. The development of artificial intelligence can then be applied in the use of public administration by the government, especially in the era of the industrial revolution 4.0. This research then aims to see how the implementation of artificial intelligence in the field of public administration in Indonesia. This research will be carried out using a descriptive qualitative approach. The method of this research uses literature study which comes from various research results and previous studies. The results of this study then found that the existence of artificial intelligence can already be felt in public administration. This can be seen from the various applications that have been issued by the government in helping people's needs. But unfortunately, the use of artificial intelligence cannot be felt by all government agencies, due to various factors, such as the large budget required. Therefore, the government as a responsible party needs to be able to overcome these various problems.